Ketahanan n-pentana dan sifat mekanis vulkanisat karet perapat dari campuran karet alam/akrilonitril-butadiena dengan kompatibiliser - Kinasih, Norma Arisanti; Fathurrohman, Muhammad Irfan (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
The improvement of the compatibility of natural rubber (NR)/acrilonitrile-butadiene rubber (NBR) blend on rubber seal vulcanizate has been done by the addition of chloroprene rubber (CR) or epoxidized natural rubber (ENR) as compatibilizer. Rubber seal compound was made of NR and NBR blend (BN) with CR (BCR), and ENR with epoxy content of 10% (BENR10), 20% (BENR20), 30% (BENR30), 40% (BENR40), and 50% (BENR50). The composition in each formula was homogenized, with comparison of NR:NBR at 40:60, and NR:compatibilizer:NBR at 40:5:55. That compounds were vulcanized with efficient system at 150oC. The addition of CR-compatilizer improved the curing characteristic, compression set, and n-pentane resistance of BN vulcanizate. Meanwhile, the addition of KAE-compatilizer improved the elasticity of BN vulcanizate. BENR elasticity and n-pentane resistance increased in line with the increasing level of epoxy content of ENR.Keywords: rubber seal, compatibilizer, n-pentane resistance, mechanical properties.Â